2022
DOI: 10.1039/d2ee01813f
|View full text |Cite
|
Sign up to set email alerts
|

Understanding and mitigating A-site surface enrichment in Ba-containing perovskites: a combined computational and experimental study of BaFeO3

Abstract: BaFeO3-based perovskites are promising cathode materials for intermediate-temperature solid oxide fuel cells and protonic ceramic fuel cells due to their high electrocatalytic activity. However, during operation Ba has been observed...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 72 publications
0
5
0
Order By: Relevance
“…In order to obtain additional information on the composition of the films, we have analyzed the stoichiometry by electron probe microanalysis (EPMA). Particularly, the stoichiometry of the PNMO films has revealed that samples grown under high oxygen pressures (PO 2 ≥ 350 mTorr) show a certain degree of Pr deficiency (not related to Pr migration as in, e.g., [ 30 ]). Cationic vacancies can have an impact on the properties of perovskite oxides [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…In order to obtain additional information on the composition of the films, we have analyzed the stoichiometry by electron probe microanalysis (EPMA). Particularly, the stoichiometry of the PNMO films has revealed that samples grown under high oxygen pressures (PO 2 ≥ 350 mTorr) show a certain degree of Pr deficiency (not related to Pr migration as in, e.g., [ 30 ]). Cationic vacancies can have an impact on the properties of perovskite oxides [ 31 , 32 ].…”
Section: Introductionmentioning
confidence: 99%
“…An ideal PCFC cathode should have high intrinsic activity for the reduction of oxygen to oxygen ions as well as high proton conductivity to increase the active reaction sites for water formation. [ 32,41,44,45 ] In our previous work, we have proved that the effect of hydration reaction on ORR in PCFCs can be negative due to the competitive adsorption between water and oxygen species over the cathode for active sites, and the decrease of oxygen partial pressure in the atmosphere by water dilution. [ 46–48 ] Therefore, we evaluated the electrocatalytic activities of single‐phase STF and a series of nanocomposite NSTF x electrodes ( x = 0.1, 0.2, 0.3, and 0.4) using proton‐conducting BZCYYb and oxygen‐ion conducting Sm 0.2 Ce 0.8 O 2 (SDC)‐supported symmetric cells.…”
Section: Resultsmentioning
confidence: 99%
“…For example, Feng et al observed a 6-fold increase in the reaction rate for the oxidation of propane using defective structures of LaCoO 3 [24]; similarly, Lindenthal et al obtained modified perovskites with Fe nanoparticles (NPs) that resulted in a CO formation-specific activity of 50 µmol•m −2 •s −1 , 3-fold higher than the undoped catalyst [25]. Additionally, A-site deficiency is useful to counterbalance their usually observed surface enrichment at the expense of B-site cations, the latter being redox active sites [26]. To further improve the catalytic activity of perovskites, surface decoration with active metals to form a metal-semiconductor heterostructure can be exploited [27,28].…”
Section: Introductionmentioning
confidence: 99%